Exercise System for the Development of Student’s Motor Capacity - Aleksandr N. Legotkin, Nikolay L. Ponomarev, Valery D. Panachev, Leonid A. Zelenin, Anatoly A. Opletin, (Opción, 2019)
This article provides recommendations for the formation and development of students’ coordination abilities in physical education classes via a special sociological questionnaire. As a result, coordination of movements with closed eyes after the standard load at t 4.43 (p <0.001); t 3.82 (p <0.001) and 3.27 (p <0.01) confirmed a high level of improvement in the development of sensory (sensitive). In conclusion, a functional model of development and assessment of the student’s coordination abilities has been created, with the help of which the targeted formation of the students’ motor and functional potential and physical activity is ensured.